The Impact of Continuous Digital Video Electroencephalogram (CEEG) Introduction on the Use of Anti-Epileptic Drugs (AEDS) in Neonates with Hypoxic Ischemic Encephalopathy (HIE). (1st June 2016) - Bashir, RA; Espinoza, L; Vayalthrikkovil, S; Buchhalter, J; Bello-Espinosa, L; Mohammad, K
Abstract: BACKGROUND: Use of AEDs in neonates may disrupt neuronal development by synaptic re-organization and altering brain plasticity. Introduction of cEEG as part of neonatal neurocritical care long term monitoring (LTM) aims to improve seizure detection and control in neo-nates with HIE. OBJECTIVES: To assess the impact of cEEG on seizure detection and the use of AEDs in neonates with HIE DESIGN/METHODS: A retrospective cohort study of neonates admitted with HIE to a level III NICU two years before and after introduction of LTM in August 2013. The cEEGs were read remotely by a pediatric epileptologist. Before LTM, a 60 minute routine EEG (rEEG) was the standard practice. Primary outcome was the number of AEDs used. Secondary outcomes were AEDs used as maintenance and on discharge, and AEDs burden (total mg/kg used during hospital stay). HIE staging was based on modified Sarnat scoring system. Drug burden for each AED was calculated. Categorical variables were analysed using Chi-square test and continuous variables using student's t test. RESULTS: n=157 (total number of HIE patients); median gestation 40 weeks (IQR 38-40); 71 infants(45%) had LTM monitoring;103 infants(66%) were cooled. Baseline and clinical characteristics including disease severity and cooling were similar. In the pre LTM era, 12 of 52 (23%) infants with clinical seizures, only 12 had seizures by rEEG . Using cEEG, 17 out of 33 (52%) clinical seizures were confirmed by cEEG; 5/36(1%) had subclinical seizures compared to none before LTM. Detection of EEG seizures increased significantly with LTM (p 0.02). Discharge on any AEDs was less in the LTM group and the mean AEDs burden was reduced from 176 mg/kg in the pre LTM to 91 mg/kg in the post LTM group. CONCLUSION: Introduction of cEEG improved seizure detection and control; but decreased the overall use and burden of AEDs. p value <0.05 is denoted as *